Aisyiyah and early childhood education: Instilling islamic values from an early age in Indonesia - Novanto, Riza Awal; Romelah, Romelah; Humaidi, M. Nurul (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2024)
This research aims to examine the role of Aisyiyah in early childhood education (PAUD) and efforts to instill Islamic values from an early age in Indonesia through a qualitative approach using the case study method. The research focuses on PAUD institutions' management, curriculum development, and the teaching methods applied. Data was collected through in-depth interviews, participant observation, and documentation at several Aisyiyah PAUD institutions in various regions in Indonesia. The research results show that Aisyiyah focuses on cognitive aspects and integrates character education and Islamic values into the curriculum. An Islamic and conducive learning environment is also created to support learning. This research also highlights the challenges Aisyiyah faces in implementing Islamic education in the modern era, such as limited resources and the influence of modern technology. Nevertheless, Aisyiyah overcame this challenge through various educational and social programs that strengthened her commitment to community development and education based on Islamic values. This research's findings can significantly contribute to developing Islamic-based early childhood education in Indonesia. Islamic religious education, starting from an early age, has a crucial role in shaping children's character and morals, ensuring they grow into individuals with strong moral and spiritual integrity.